Olfactory disorders in patients with chronic rhinosinusitis in Kinshasa, Democratic Republic of the Congo: A cross-sectional study - Yasmin Nsunzu Tshingamb; Sympho Junior Mpiana; Patrick Sekele Marob Ndjock; Emile Kayembe; Eric Banza Lukoji; Alain Ntumba Malemba; Auguste O. Omadjela; Dieudonné T. Nyembue (Orapuh Journal)
Introduction